Assessing Correlation between Spiritual Wellbeing and Stress of Mothers of Hospitalized Newborns in Neonatal Intensive Care Units - A Vafaei Fooladi; M Rassouli; F Yaghmaie; N Shakeri (Iran University of Medical Sciences, 2015)
Abstract Background & Aim: Every year a large number of premature and sick infants admitted to the neonatal intensive care units. This is a stressful event for parents and especially the mother. There is a small amount of information relating to the factors associated with maternal stress in the NICU. As Spirituality is a source of energy and power to cope with stress, the aim of this study was to determine correlation between spiritual wellbeing and stress in mothers of hospitalized newborns in the NICU. Material & Method: In this descriptive correlational study, 180 mothers of hospitalized newborns in selected hospitals affiliated to Shahid Beheshti University of Medical Sciences were recruited by convenience sampling method. Data collection tools included Demographic characteristics questionnaire, "Parental Stressor Scale: NICU" (PSS: NICU) and "Spiritual well Being Scale" (SWBS). Data were analyzed with SPSS/16 and statistical tests including Descriptive statistics and Pearson's correlation were used. Results: The results showed that most of mothers (56.7%) had moderate stress, and 25 percent experienced severe stress. Also, most of the mothers participating in present study (51.1%) had a very high spiritual wellbeing. There was a significant adverse correlation between stress of mothers and her spiritual wellbeing (r= -0.48, p<0.001). Conclusion: This study has determined correlation between spiritual wellbeing and stress in mothers of hospitalized newborns in the NICU. According to the findings of this research, neonatal special nurses can reduce stress of mothers with identifying mothers who are at risk for stress and providing spiritual support to them.